PENGEMBANGAN BUKU SAKU TANAMAN OBAT DEGENERATIF PADA MASYARAKAT DI DESA PENANDINGAN KECAMATAN PSEKSU KABUPATEN LAHAT - Shelby Okta Khoriza; Destien Atmi Arisandy; Yunita Wardianti (Yayasan Nusantara Hasana Berdikari, 2023)
This study aims to determine the development process as well as the validity and practicality of pocket books of degenerative medicinal plants in Penandingan Village, Pseksu District, Lahat Regency. This research is included in Research Development using the Borg and Gall development model. Based on the results of research conducted in the Penancingan Village Area, 41 types of degenerative medicinal plants were obtained. The data obtained was then developed into a Pocket Book by going through several stages, namely preliminary product development and validation by 3 experts namely linguists, media experts and material experts. Validation of the Pocket Book of Degenerative Medicinal Plants was carried out by 3 expert lecturers from PGRI Silampari University, namely material experts obtained a score of 48 with a percentage of 80% which was included in the